2019
DOI: 10.1088/1742-6596/1247/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

A Structure-from-Motion Pipeline for Generating Digital Elevation Models for Surface-Runoff Analysis

Abstract: Digital Elevation Models (DEMs) are used to derive information from the morphology of a land. The topographic attributes obtained from the DEM data allow the construction of watershed delineation useful for predicting the behavior of systems and for studying hydrological processes. Imagery acquired from Unmanned Aerial Vehicles (UAVs) and 3D photogrammetry techniques offer cost-effective advantages over other remote sensing methods such as LIDAR or RADAR. In particular, a high spatial resolution for measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This supplements intensive surveying of species and also expands the potential application of field survey methods, while accounting for changes in vegetation over time [12]. In addition to the applications of multispectral sensors, RGB (Red, Green, Blue) cameras can also capture elevation data using recent improvements in point cloud reconstruction methods, such as Structure from Motion [13], detecting microtopographical variations and generating accurate digital elevation models [14].…”
Section: Introductionmentioning
confidence: 99%
“…This supplements intensive surveying of species and also expands the potential application of field survey methods, while accounting for changes in vegetation over time [12]. In addition to the applications of multispectral sensors, RGB (Red, Green, Blue) cameras can also capture elevation data using recent improvements in point cloud reconstruction methods, such as Structure from Motion [13], detecting microtopographical variations and generating accurate digital elevation models [14].…”
Section: Introductionmentioning
confidence: 99%
“…Whether commercial or FOSS, SfM-MVS software offer an opportunity for the conservation community to engage in new and novel remote sensing techniques. They can be utilised to create highly detailed maps and 2.5/3D data at local scales, now include FOSS options that are being successfully deployed for scientific research (3,4,5358,62,105) and can be incorporated into the existing FOSS remote sensing pipeline. With applications for Android smartphones such as the UAV Toolkit (67) or small, lightweight action cameras now available, combined with balloons, kites, drones, or even collecting data on the ground, there is an opportunity within the conservation sphere to start enabling remote sensing even at a grass-roots or community level, or in any situation where funding may be limited but this type of data desired.…”
Section: Resultsmentioning
confidence: 99%
“…MicMac is the more mature software of the two and was initially developed in 2003 by the French National Geographic Institute and French national school for geographic sciences (52) whereas ODM began as a concept presentation at the 2014 FOSS4G (Free and Open Source Software for Geospatial) conference in Seoul. Both have drawn attention from the scientific community, but with ODM being the newer option, the focus has primarily been on its development and initial quality testing (3,4,53,54). MicMac’s maturity has allowed for a deeper scrutiny (55,56), has been utilised as the primary SfM-MVS option in geomorphological studies (57) and has been shown to be comparable to both Pix4D and Agisoft Photoscan (Metashape) within a low sward grassland study (58).…”
Section: Open Source Sfm-mvsmentioning
confidence: 99%
See 1 more Smart Citation